Exclusion Spirometry: An Initiative to Increase Lung Function Assessment in Primary Care - José Almirall; Paul Bégin (Canadian Respiratory Journal)
Ongoing spirometry quality standards are difficult to bring into the daily routine of general practice. As a result, spirometry is rarely performed by primary care physicians. A new approach is proposed: exclusion spirometry. Acceptable and reproducible results are sought. However, the goal of the test is to try to reach values within normal limits, even if results do not reach quality standards. Normal results would be sufficient to exclude respiratory impairment, except in asthma. Abnormal results would require further testing in a diagnostic spirometry laboratory. The aim of the initiative is to enhance the compliance of general practitioners in using spirometers for screening.